Largemouth bass predators reduce growth, feeding and movement in juvenile channel catfish - Fine, M.L; Mayo, M.S; Newton, S.H; Sismour, E.N (Ecology of freshwater fish, 2011)
Fine ML, Mayo MS, Newton SH, Sismour EN. Largemouth bass predators reduce growth, feeding and movement in juvenile channel catfish. Ecology of Freshwater Fish 2011: 20: 114-119. © 2010 John Wiley & Sons A/S Abstract - Animals utilise sensory cues to make decisions that will decrease their vulnerability to predation. With a well-developed olfactory system and taste buds located inside the mouth and on the external body surface, catfishes are excellent subjects to investigate nonconsumptive predator effects. Juvenile channel catfish Ictalurus punctatus are often eaten by largemouth bass Micropterus salmoides, and we tested the hypothesis that largemouth bass fed catfish would adversely affect foraging and growth in channel catfish. Groups of catfish were placed in tanks partitioned by a mesh screen: experimental tanks had a largemouth bass on the other half of the tank, and control tanks had an empty chamber. Experimental catfish exhibited a long-term decrease in spontaneous motion, feeding and growth. Feeding catfish to the bass caused the experimental catfish to freeze after a multi-second latency suggesting transport of an alarm cue. Thus, there were long-term effects from the continuous presence of the bass and additional short-term cues from the bass consuming a catfish.